TEXT AS A UNIT OF TEACHING COHERENT WRITTEN SPEECH IN RUSSIAN AS A FOREIGN LANGUAGE CLASSES - Uktamboy Kalandarov; Rustam Egamov (Bright Mind Publishing, 2025)
The article is devoted to the problem of teaching students of a foreign language audience writing as the main type of speech activity in Russian language classes. One of the effective means of learning new language material and mastering all speech activities is an educational text. This article examines the features of organizing work on a text in Russian as a foreign language classes.
Keywords: Text, speech activity, speech competence, written communication, speech exercises, reproductive tasks, production